Optical grid networking exploiting path computation element (PCE) architecture. (1st September 2010) - Cugini, Filippo; Xu, Sugang; Harai, Hiroaki; Paolucci, Francesco; Valcarenghi, Luca; Castoldi, Piero
A dynamic and joint optimisation of computational and network resources may significantly improve the performance of grid-enabled applications. In this paper, the path computation element protocol (PCEP) is first proposed as standard grid network service interface between grid resource manager (GRM) and network resource manager (NRM). Then, two different schemes exploiting the PCEP protocol and the PCE capability to provide synchronised and optimal path computations are proposed. The schemes allow the GRM to exploit performance metrics representative of the expected network resource utilisation and to perform a jointly optimal choice of both computational and network resources. Simulation results show that the proposed schemes significantly improve the overall amount of successfully established grid services. Experimental implementations on the 'JGN2plus' testbed are presented to show that the proposed schemes avoid control plane extensions or interfaces specifically designed for grid purposes and do not substantially affect the overall grid service delivery time.